2018
DOI: 10.1371/journal.pone.0203495
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and spectrum of AKT1, PIK3CA, PTEN and TP53 somatic mutations in Chinese breast cancer patients

Abstract: Breast cancer, one of the most frequently occurring cancers worldwide, is the leading cause of cancer-related death among women. AKT1, PIK3CA, PTEN and TP53 mutations were common observed in breast cancer representing potential clinical biomarkers for cancer classification and treatment. A comprehensive knowledge of AKT1, PIK3CA, PTEN and TP53 mutations in breast cancer was still insufficient in Chinese population. In this study, the complete coding regions and exon-intron boundaries of AKT1, PIK3CA, PTEN and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…PIK3CA pathway is one of the most frequently deregulated pathways in breast cancer and has been implicated in breast tumor development, progression and therapeutic resistance (26). Somatic mutations in PIK3CA have been demonstrated to be associated with HR-positive (either ER-positive or PRpositive)/HER2−negative breast tumors (26)(27)(28)(29). An increase in PIK3CA mutations have been observed in relapsed breast tumors as compared to primary breast tumors (30).…”
Section: Figure 4 | Correlation Between Clinical and Molecular Featurmentioning
confidence: 99%
“…PIK3CA pathway is one of the most frequently deregulated pathways in breast cancer and has been implicated in breast tumor development, progression and therapeutic resistance (26). Somatic mutations in PIK3CA have been demonstrated to be associated with HR-positive (either ER-positive or PRpositive)/HER2−negative breast tumors (26)(27)(28)(29). An increase in PIK3CA mutations have been observed in relapsed breast tumors as compared to primary breast tumors (30).…”
Section: Figure 4 | Correlation Between Clinical and Molecular Featurmentioning
confidence: 99%
“…The lipid phosphatase activity of the PTEN protein antagonizes the phosphatidylinositol 3‐kinase signaling pathway, while protein phosphatase activity inhibits the MAPK pathway (Weng, Brown, & Eng, 2001a; Weng, Smith, Brown, & Eng, 2001b). Somatic PTEN mutations play an important role in the development of multiple cancer types (Li et al., 2018). However, in 1997, Liaw et al.…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment conducted on men with prostate cancer, it was found that PTEN loss is associated with metastasis and invasion of cancer cells, and undesirable prognosis [ 68 ]. In another experiment in China, on breast cancer patients, occurrence of PTEN mutation is 4.8% [ 69 ]. PTEN can be used as a biomarker for response of patients with cancer into chemotherapy.…”
Section: Pten In Clinical Studiesmentioning
confidence: 99%